Teaching and Learning Programming - H.M. Havenga (Empowering IT & CAT Teachers, 2013)
The learning of computer programming is difficult and therefore teachers are required to support learners. This implies that the teacher needs to use various skills, strategies and activities to scaffold the learning of programming. The purpose of this chapter is to provide guidelines in teaching computer programming. Many learners are very excited to begin working on the computer, and want to develop programs by starting to code immediately. However, it is important that they should plan a program and ensure the logic is correct before starting to code. Algorithms and trace tables are used to direct programming logic and evaluate